Estimating the impact of climate change on residential water use using panel data analysis: a case study of Lilongwe, Malawi - Makwiza, Chikondi; Fuamba, Musandji; Houssa, Fadoua; Jacobs, Heinz Erasmus (Journal of water, sanitation, and hygiene for development, 2018)
In this study, panel linear models were used to develop an empirical relationship between metered household water use and the independent variables plot size and theoretical irrigation requirement. The estimated statistical model provides a means of estimating the climate-sensitive component of residential water use. Ensemble averages of temperature and rainfall projections were used to quantify potential changes in water use due to climate change by 2050. Annual water use per household was estimated to increase by approximately 1.5% under the low emissions scenario or 2.3% under the high emissions scenario. The model results provide information that can enhance water conservation initiatives relating particularly to outdoor water use. The model approach presented utilizes data that are readily available to water supply utilities and can therefore be easily replicated elsewhere.